Evaluación del estado nutricional de los niños y niñas de la Escuela Tnte Hugo Ortiz N°1 de la ciudad de Loja, y su relación con el hematocrito, hemoglobina, albumina y proteinas totales. - Enríquez Díaz, Diana Erminia (2013)
EVALUATION OF THE NUTRITIONAL STATUS OF CHILDREN OF SCHOOL LIEUTENANT TNTE. HUGO ORTIZ N° 1 IN THE CITY OF LOJA, AND ITS RELATION TO HEMATOCRIT, HEMOGLOBIN, ALBUMIN AND TOTAL PROTEIN, the present study is carried out it with the purpose of, to evaluate the nutritional status of children of school lieutenant Tnte. Hugo Ortiz n° 1 in the city of Loja, and its relation to hematocrit, hemoglobin, albumin and total protein, study that was of descriptive , prospective in 163 niños/as understood in the age of 6-11 years and framed in the inclusion approaches and exclusion. Reaching the following conclusions; that of the studied population 1 % hemoglobin diminished <11,2gr/dl; in what concerns to the proteins total 7% I am increased >8.0gr/dl that is to say, 7 diminished% <5,9gr/dl; based on the albumin 8% increased >5,0gr/dl, 6% diminished <3,5gr/dl respectively. Anthropometric data allowed to know that 2% of the scholars have overweight, 2% lowers weight, and at the same time one could observe that 96% of children and girls are inside the normal parameter of IMC. Keywords: School-age children, nutritional status, anthropometric data, hematocrit, hemoglobin, total protein and albumin.